Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s11999-009-1161-7
|View full text |Cite
|
Sign up to set email alerts
|

Does the Taylor Spatial Frame Accurately Correct Tibial Deformities?

Abstract: Background Optimal leg alignment is the goal of tibial osteotomy. The Taylor Spatial Frame (TSF) and the Ilizarov method enable gradual realignment of angulation and translation in the coronal, sagittal, and axial planes, therefore, the term six-axis correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
88
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 43 publications
2
88
3
Order By: Relevance
“…In the ISKD group 50% of patients had A quality and 17% had C quality at 8 weeks. Not all studies use a standardized method of assessing the quality of bone regenerate during distraction; however, some have described the risk of development of poor regenerate bone [7,8,11,12,18,22,24] with a lengthening rate faster than 1 mm per day. Kenawey et al [10] proposed other risk factors associated with poor bone regenerate from their analysis of 37 femoral ISKD lengthenings for which insufficient bone regenerate developed in eight patients (23%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ISKD group 50% of patients had A quality and 17% had C quality at 8 weeks. Not all studies use a standardized method of assessing the quality of bone regenerate during distraction; however, some have described the risk of development of poor regenerate bone [7,8,11,12,18,22,24] with a lengthening rate faster than 1 mm per day. Kenawey et al [10] proposed other risk factors associated with poor bone regenerate from their analysis of 37 femoral ISKD lengthenings for which insufficient bone regenerate developed in eight patients (23%).…”
Section: Discussionmentioning
confidence: 99%
“…Mahboubian, M. Seah, A. T. Fragomen, S. R. Rozbruch (&) Limb Lengthening and Complex Reconstruction Service, Hospital for Special Surgery, 535 East 70th Street, New York, NY 10021, USA e-mail: Srroz@optonline.net; rozbruchsr@hss.edu lengthening was developed, the complication rates have diminished with time and the development of new technology [16,[18][19][20]. However, the time required to wear the external fixator can be lengthy [17] and cumbersome for patients [14,21,22]. Modern methods such as lengthening over a nail (LON) and internal lengthening devices (eg, the ISKD, [Intramedullary Skeletal Kinetic Distractor: Orthofix Inc, McKinney, TX, USA]) have been developed to decrease or eliminate the time required for a patient to wear a frame [4].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Ilizarov-type external fixators require the sequential correction of each component of the deformity due to the limited mobility of the device. Some spatial fixators require an initial correction based on mounting following residual deformity correction [21,22]. Smart Correction software is intended to correct all deformities in one step, regardless of the mounting parameters.…”
Section: Discussionmentioning
confidence: 99%
“…TSF can also be used to treat malunion or nonunion [7] as well as fractures [18]. However, these studies concluded that the combination of a stable external fixation device and the accuracy of the computer-based technology make the treatment suitable for precise correction of skeletal deformities [4,19]. Ferreira et al [8,9] reported on the Ilizarov external fixator for multiplanar foot deformities.…”
Section: Discussionmentioning
confidence: 99%